Clinical Benefits of Metronomic Chemotherapy in Platinum-Refractory, Recurrent, and Metastatic Head and Neck Squamous Cell Carcinoma - Amira Elwan; Adel Bakry; Mohamed Eesa; Hoda Ismail; Mohamed Alnemr (Middle East Journal of Cancer)
Background: Patients with platinum-refractory disease who experience early treatment failure of head and neck squamous cell carcinoma (HNSCC) exhibit a dismal prognosis. Metronomic chemotherapy is a promising treatment schedule in clinical practice for HNSCC. Oral metronomic chemotherapy with methotrexate, celecoxib, and capecitabine regimens was effective because of overcoming drug resistance and antiangiogenesis effects. We aimed to improve treatment outcomes of recurrent, platinum–resistant, and metastatic HNSCC.Method: In this prospective clinical trial, 94 patients diagnosed with advanced/recurrent HNSCC were enrolled. Patients received triple therapy, including capecitabine, methotrexate, and celecoxib. The multidisciplinary team evaluated treatment toxicity, response, progression-free survival (PFS), and overall survival (OS). Kaplan Meier curve was used to show the survival/Wilcoxon signed-rank test.Results: The most common observable toxicity findings were grade 1 plus grade 2 fatigue in 49 (52.1%), oral mucositis in 40 patients (42.5%), and anemia in 37 patients (39.4%) in the absence of notified grade 3 or 4 toxicities. 20 patients out of 94 exhibited complete responses (CRs). One and two-year PFS rates were 16% and 11.7%; and one and two-year OS were 21.3% and 17 %, respectively. Two median years PFS was 4 months, and two median years OS was 8 months (SPSS 16.0 for Windows, Wilcoxon signed-rank test, P value ≤ 0.05 is significant).Conclusion: Capecitabine, methotrexate, and celecoxib combined chemotherapy are effective and tolerable in treating platinum-refractory, recurrent, and metastatic HNSCC with non-inferior clinical outcome results, especially in poor societies.